2022
DOI: 10.1007/s00261-022-03549-7
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of abdominal simultaneous multi-slice accelerated diffusion-weighted imaging with motion-correction in patients with cystic fibrosis and impaired compliance

Abstract: Objectives The aim of this prospective study was to compare scan time, image quality, signal-to-noise Ratio (SNR), and apparent diffusion coefficient (ADC) values of simultaneous multi-slice accelerated diffusion-weighted imaging with motion-correction (DWI SMS Moco) to standard diffusion-weighted imaging (sDWI) in free-breathing abdominal magnetic resonance imaging (MRI) in pediatric and young adult patients with cystic fibrosis (CF). Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…In this study, the ADC values showed no significant differences in six of seven localizations analyzed. This is in agreement with the results of Glutig et al [ 24 ] and Xu et al [ 32 , 33 ], but contrasts with the data of Taron et al [ 19 ], who measured lower ADC values.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the ADC values showed no significant differences in six of seven localizations analyzed. This is in agreement with the results of Glutig et al [ 24 ] and Xu et al [ 32 , 33 ], but contrasts with the data of Taron et al [ 19 ], who measured lower ADC values.…”
Section: Discussionsupporting
confidence: 91%
“…They were able to show a substantial reduction in liver DWI scan time (70%), with comparable image quality. Recently, regarding abdominal MRI in children and adolescents with cystic fibrosis, Glutig et al showed a 32% reduction in examination time with no decrease in SNR using SMS-DWI and improved image quality by additional reconstruction with motion-correction [ 24 ]. In this work, the combination of STIR-DWI and the SMS technique for whole-body imaging was used for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, similar to our increased detection rate using EIP, they also found increased sensitivity for the complexedaveraged images (73.6% vs. 63.1% in acquired and 68.4% vs. 63.1% in calculated images). Besides implementing the proposed EIP in DWI of the prostate, the technique can also be used in different areas of the body and similar improvements in image quality and lesion detection rates were reported [15][16][17]. Tavakoli et al have found improved image quality, lesion discernibility, and reduced acquisition times for renal imaging with simultaneous multislice (SMS) DWI with respiratory triggering compared with standard single-shot DWI [17].…”
Section: Discussionmentioning
confidence: 75%
“…In addition to the conventional reconstruction, the acquired data were also processed by a scanner-integrated research application that included further steps in the derivation of combined diffusion-weighted images from multiple complex-valued averages with different diffusion weighting, which was developed with a focus on free-breathing acquisitions. As detailed in a previous report [ 11 ], the processing first performed an elastic two-dimensional registration of averages with the same b-value and slice position. Furthermore, based on the variations between these averages, the regional signal compensation due to locally corrupted averages was estimated.…”
Section: Methodsmentioning
confidence: 99%